2010
DOI: 10.1111/j.1751-7176.2010.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Practices of Resident Physicians Regarding Hypertension in the Inpatient Setting

Abstract: Hypertension is prevalent in the population at large and among hospitalized patients. Little has been reported regarding the attitudes and patterns of care of physicians managing nonemergent elevated blood pressure (BP) among inpatients. Resident physicians in internal medicine (IM), family medicine (FM), and surgery were surveyed regarding inpatient BP management. One hundred eighty-one questionnaires were completed across 3 sites. Respondents generally considered inpatient BP control a high priority. A major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…36,37 Even though there is no substantive evidence that antihypertensive medications improve outcomes of hospitalized patients who develop HTN, physicians believe it is important. 6 This could be due to fear that untreated HTN could progress to end organ damage or healthcare providers not being aware of the risks of overtreatment. 38 However, a retrospective analysis of veterans admitted for non-CVD causes found an increased rate of 30-day adverse events and readmissions as well as higher 1-year risk of CVD events among patients who had their antihypertensive treatment intensified during inpatient admissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36,37 Even though there is no substantive evidence that antihypertensive medications improve outcomes of hospitalized patients who develop HTN, physicians believe it is important. 6 This could be due to fear that untreated HTN could progress to end organ damage or healthcare providers not being aware of the risks of overtreatment. 38 However, a retrospective analysis of veterans admitted for non-CVD causes found an increased rate of 30-day adverse events and readmissions as well as higher 1-year risk of CVD events among patients who had their antihypertensive treatment intensified during inpatient admissions.…”
Section: Discussionmentioning
confidence: 99%
“…However, far more common is incident severe HTN in already hospitalized patients occurring during an admission unrelated to HTN 3–5 . Increased blood pressure (BP) in ambulatory patients is associated with increased risk of cardiovascular disease (CVD) related outcomes including stroke, myocardial infarction and coronary artery disease increases, but treatment of severe inpatient HTN in the absence of acute target organ injury is currently not directed by guidelines 6,7 . Additionally, recent studies have found that treatment of severe inpatient HTN resulted in greater BP drops, and higher rates of acute kidney injury and myocardial injury 5,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many residents (44%) considered drugs should be started or adjusted if the systolic blood pressure was mildly high (140-159 mmHg) and that patients with in-hospital blood pressure elevations should be discharged on the antihypertensive regimen prescribed in hospital (91%). 11 In another survey, about a third of hospital doctors would transfer an asymptomatic patient to an intensive care unit because of high blood pressure even in the absence of target organ damage. The average blood pressure that would prompt the transfer was 210/117 mmHg for house officers and 193/110 mmHg for other hospital doctors.…”
Section: Physicians' Attitudes Towards In-hospital Hypertensionmentioning
confidence: 99%
“…3 Among internal medicine and family medicine trainees in one survey, nearly half reported that they would use IV medications in a scenario where an inpatient had an asymptomatic blood pressure above 180 mm Hg. 4…”
Section: Introductionmentioning
confidence: 99%